Ecological aspects of black-pincelled marmoset (Callithrix penicillata) in the cerradão and dense cerrado of the Brazilian Central Plateau - MIRANDA, G. H. B. de (2001)
Ecological data about three free-ranging groups of C. penicillata (black-pincelled marmoset) were observed between March and December 1996, in one cerradão patch (in the Ecological Reserve of Brazilian Institute of Geography and Statistics, RECOR) and two patches of dense cerrado (one in the Recor and another in the Botanical Garden of Brasília, JBB), situated in the APA (area of environmental protection) of the Gama/Cabeça-de-Veado, Distrito Federal. Each area was visited weekly during three periods of two months -- end of the rainy season (01/04 to 31/05), dry season (16/06 to 15/08) and beginning of the rainy season (14/10 to 15/12) -- and instantaneous scan records at fifteen minute intervals were made for the vertical and horizontal position of each visible individual of the target group. The group size ranged between 4 and 11 elements. In September, the birth of twins in both groups of the Recor was observed. Home-range varied from 8.25 to 18.5 hectares, while density ranged from 0.4 to 0.82 ind/ha. Twenty two species of nine tree families were identified as exudate sources. Qualea grandiflora (Vochysiaceae), Vochysia thyrsoidea (Vochysiaceae), Scheflera macrocarpum (Araliaceae) and Qualea parviflora (Vochysiaceae) were more explored. Fruits (14 species, two of which were exotics), nectar, honey, arthropods (mainly orthopterans) and bird eggs complete their diet. The main sleep-tree species was Emmotum nitens (Icacinaceae). Data from different seasons and studied groups/areas were compared along previous data from this primate species in gallery forests. In the cerradão and dense cerrado areas C. penicillata had a similar group size, however a larger home-range and smaller density than in gallery forests were observed in this study.